Is length of stay in hospital a stable proxy for injury severity?. Issue 4 (29th June 2010) - Cryer, C; Gulliver, P; Langley, J D; Davie, G
Abstract : Research question: Is length of stay (LoS) in hospital a stable proxy for severity of injury when monitoring time trends in serious injury incidence? Objective: To investigate whether LoS metrics (mean, median and proportion exceeding several LoS thresholds) have changed over time for injury diagnoses with known severity. Design: Time series investigation. Subjects and setting: New Zealand population admitted to hospital for injury and discharged during the period 1989 to 1998. Main outcome measures: Interpolated median and geometric mean lengths of stay, as well as the proportion of cases that have an LoS greater than or equal to 3, 4, 7 and 14 days in hospital. Methods: ICD-9-CM diagnoses that are approximately homogeneous in regard to severity of injury (ICD-HS diagnoses) were identified. Trends were investigated in the LoS statistics for: injury and non-injury diagnoses combined; all injury diagnoses; major body sites of injury; severity strata; and ICD-HS diagnoses. Results: Almost without exception, there was a decline in the LoS statistics over time for all diagnoses, all injury diagnoses, each body site of injury investigated, severity strata, and the ICD-HS diagnoses. Conclusions: Reductions in median and geometric mean LoS over time, as well as reductions in the proportion exceeding selected LoS thresholds, were due to factors other than reductions in the incidence of serious injury; for example, changes in service delivery over time. An LoS threshold should not be used as a proxy for severity of injury if the goal is to monitor time trends in injury incidence.